MULTIDISCIPLINARY APPROACH TO THE CONSERVATIVE TREATMENT OF CHILDREN WITH OSTEOGENESIS IMPERFECTA AT THE NATIONAL CHILDREN’S MEDICAL CENTER (Herald of the National Children's Medical Center, 2025)
Osteogenesis imperfecta (ICD-10 Q78.0) is a hereditary connective tissue disorder characterized by bone fragility, multiple fractures, and skeletal deformities. In 85–90% of cases, mutations are found in the COL1A1 and COL1A2 genes. The disease may follow autosomal dominant, autosomal recessive, or X-linked patterns of inheritance. Its prevalence is estimated at 1 in 10,000 to 1 in 20,000 live births. The modern classification includes 18 types of the disease according to Sillence.
Keywords: osteogenesis imperfecta; osteoporosis; bisphosphonates; skeletal deformities; multidisciplinary therapy